2014
DOI: 10.4236/health.2014.613194
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of an Exercise Instructor or Group Members Affects Physical Self-Concept and Physical Self-Esteem: An Experimental Study in the Elderly

Abstract: Background: Physical self-concept and physical self-esteem are important sources of general selfesteem and overall health. Evidence indicates that exercise leads to an enhancement in physical self-concept and physical self-esteem. Until now however, it remained unclear whether the beneficial effects of exercise were impacted by different types of exercise environments. Thus, the purpose of this study was to experimentally investigate, whether the presence or absence of an instructor or other group members infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…It is also plausible that the presence of the group instructor within the FlexToBa DVD provided specific support for improving both perceptions of physical self-worth and physical condition. This is supported by previous research in which improvements in esteem were observed in the context of an individualized, instructor-led exercise condition compared to a group setting (33). Importantly, our program was able to successfully target sources of self-efficacy information via DVD to mirror previous findings from center-based programs (15; 34) and extend them into the home, easing the burden on both participants and research staff and increasing the potential for scalability (see Exercise Log, Exercise Prescription, and Feedback Form, Supplemental Digital Content 1, which illustrate elements of self-efficacy targeted in the current study).…”
Section: Discussionsupporting
confidence: 85%
“…It is also plausible that the presence of the group instructor within the FlexToBa DVD provided specific support for improving both perceptions of physical self-worth and physical condition. This is supported by previous research in which improvements in esteem were observed in the context of an individualized, instructor-led exercise condition compared to a group setting (33). Importantly, our program was able to successfully target sources of self-efficacy information via DVD to mirror previous findings from center-based programs (15; 34) and extend them into the home, easing the burden on both participants and research staff and increasing the potential for scalability (see Exercise Log, Exercise Prescription, and Feedback Form, Supplemental Digital Content 1, which illustrate elements of self-efficacy targeted in the current study).…”
Section: Discussionsupporting
confidence: 85%